Analysis of Student Learning Outcomes by Applying the Example Non Example Learning Model: Social Interaction Studies - Sefnath Nuniary; Eliseba Lartutul (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2022)
The purpose of this study is to analyze student learning outcomes by using the Example Non Example learning model in social interaction material. The research design used in this research is the One-Group Pretest-Postest Design. The data used is only from a comparison of pretest and posttest results on the concept of social problems through the Example Non Example learning model with the On-Group Pretest-Posttest design. The results showed that there were differences in the average results of learning sociology before and after using the example non example learning model. As for future suggestions, namely the current learning process, teachers must be more observant in seeing and considering suitable learning methods or models to be used in arousing student enthusiasm for learning which is carried out offline or online.